Physician Burnout among Members of the Society for Maternal-Fetal Medicine - Hughes, Francine; Francis, Antonia P.; Sciscione, Anthony C. (American Journal of Perinatology, 2019)
Objective This study aimed to determine the rate of physician burnout among maternal-fetal medicine subspecialists and identify associated factors.Study Design Noninternational members of the Society for Maternal-Fetal Medicine (SMFM) were surveyed regarding burnout using a validated tool specifically designed for health professionals (Maslach Burnout Inventory—Human Services Survey). Burnout was defined as exceeding established cutoffs for emotional exhaustion or depersonalization. Demographic information and potential contributors associated with the presence of burnout were also examined.Results The survey was sent to 1,220 members and 44.1% of members completed the entire survey. The physician burnout rate was 56.5%. Factors associated with burnout included female gender, being 5 to 20 years in practice, self-perceived burnout, being somewhat or very dissatisfied with career or supervisor and charting for more than 4 hours per day. Factors associated with less burnout were being male, having some protected time for education and regular exercise. Women scored higher on emotional exhaustion and depersonalization and lower personal accomplishment compared with men.Conclusion Physician burnout among the SMFM members is higher than has been reported in other specialties. While some of these factors are modifiable, further study into why women have higher rates of burnout needs to be performed.
Keywords: physician burnout; career satisfaction; obstetrics and gynecology; maternal-fetal medicine